Experimental evaluation of primary measures for NOX and dust emission reduction in a novel 200 kW multi-fuel biomass boiler. (June 2021) - Archan, Georg; Anca-Couce, Andrés; Buchmayr, Markus; Hochenauer, Christoph; Gruber, Johann; Scharler, Robert
Abstract: The aim of this work is to utilize various biogenic fuels without ash slagging and to significantly reduce NOX and particulate matter emissions in comparison to modern combustion technologies. For this purpose, a novel small-scale multi-fuel biomass grate furnace technology was developed and experimentally investigated. It employs a low oxygen concentration in the fixed-bed and a double air staging, including the supply of flue gas recirculation. In this way slagging is prevented on the grate, reducing the release of ash-forming volatiles, NOX emissions are minimized in the reduction zone and an efficient flue gas burnout is achieved in the tertiary zone. Wood pellets and chips as well as miscanthus briquettes were investigated. The measured total particle emissions showed a reduction of 68% for pellets and 70% for wood chips compared to typical small-scale furnaces. Furthermore, a reduction of NOX emissions of 39% for wood chips, 40% for wood pellets and 45% for miscanthus briquettes was achieved compared to typical small-scale furnaces. The experimental parameter study provided fundamental insights into the various mechanisms involved in this novel technology, which is close to market introduction, and proved its high fuel flexibility and great potential for particulate matter and NOX emission reduction. Highlights: Development of a fuel flexible biomass combustion technology with low emissions. Compact bed design with low oxygen concentration worked as an efficient dust filter. Supply of recirculated flue gas below the grate leads to high fuel flexibility. Lowest NOX emissions due to an air ratio in the secondary zone between 0.8 and 0.9 Supply of recirculated flue gas above the grate leads to even lower NOX emissions.